Early Pediatric Fractures in a Universally Insured Population within the United States - Jared A. Wolfe; Heather Wolfe; Amanda Banaag; Scott Tintle; Tracey Perez Koehlmoos (BMC, 2019)
Abstract Background Musculoskeletal injury, including fracture, is one of the most common causes of morbidity in pediatric patients. The purpose of this epidemiologic study is to determine the prevalence and risk factors for fracture in a large cohort of pediatric patients under the age of 5. Results Of the 233,869 patients included in the study, 13,698 fractures were identified in 10,889 patients. The highest annual incidence was in the 4 year old age group with a rate of 24.2 fractures per 1000 children. The annual incidence within all age groups was 11.7 fractures per 1000 children. The two most common fractures were forearm and humerus fractures. Fracture incidence was increased in male children, patients who live outside the US, and in Caucasian patients. An increase in rate of fracture was also identified in children of officers when compared with children of enlisted service members. There were 35 abuse related fractures in our cohort, with 19 of them occurring in children less than 1 year old. Only three children in our cohort had Osteogenesis Imperfecta. Conclusion Fractures are common injuries in young children with an incidence over the first 5 years of life of 5.86%. Multiple risk factors were also identified including age, race, geographic location and socioeconomic status. The results of this study are an important contribution to epidemiologic and public health literature and serve to characterize the incidence of and risk factors for sustaining an early childhood fracture.